Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2527/jas.2014-8796
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the efficacy of flunixin meglumine and meloxicam for lame sows using a GAITFour pressure mat and an embedded microcomputer-based force plate system1

Abstract: Pain associated with lameness on farm is a negative affective state and has a detrimental impact on individual farm animal welfare. Animal pain can be managed utilizing husbandry tools and through pharmacological approaches. Nonsteroidal anti-inflammatory drugs including meloxicam and flunixin meglumine are compounds used in many species for pain management because they are easy to administer, long lasting, and cost-effective. Assessing an animal's biomechanical parameters using such tools as the embedded micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…At an oral dose of 0.5 mg/kg, it has been shown that mean peak plasma concentration is 1070 ng/ml in mature swine 25 whereas we were able to show a peak of 1300 ng/ml. Meloxicam at 0.4 mg/kg has been shown to produce some postoperative analgesia after surgical castration of young piglet 39 and at 1 mg/kg has provided analgesia in sows after lameness induction 40 . The drug release study in pigs shows promise, though future tailoring of the release kinetics will be required for successful translation.…”
Section: Discussionmentioning
confidence: 99%
“…At an oral dose of 0.5 mg/kg, it has been shown that mean peak plasma concentration is 1070 ng/ml in mature swine 25 whereas we were able to show a peak of 1300 ng/ml. Meloxicam at 0.4 mg/kg has been shown to produce some postoperative analgesia after surgical castration of young piglet 39 and at 1 mg/kg has provided analgesia in sows after lameness induction 40 . The drug release study in pigs shows promise, though future tailoring of the release kinetics will be required for successful translation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to injection, all 3 horses were found clinically sound. Soundness was defined as the ability to move freely using 4 limbs and showing no evidence of abnormal weight-shifting, non-weight-bearing behavior, and/or reluctance to walk on any limb ( Pairis-Garcia et al, 2015 ). Horses demonstrated no additional signs of systemic disease during the testing period.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in sensitivity to this noxious stimulus may correspond to increased sensitivity of nociceptors at the test site and is interpreted as increased sensitivity at the test site. Since animals are unable to state when they feel pain the mechanical nociceptive threshold (MNT) is recorded instead of the PPT, this is the amount of pressure needed to produce a pre-determined behavioral response indicative of pain ( 11 ). The use and experience of this tool in people lends additional validity to its interpretation as an indicator of pain in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure algometry has been used to assess pain and effectiveness of analgesia for research purposes in a range of farm animal species, including pigs ( 11 ) and sheep ( 12 ). In cattle, it has been used to assess pain sensitivity in dairy cattle with mastitis ( 13 ), lameness ( 14 16 ); and following dehorning ( 7 ).…”
Section: Introductionmentioning
confidence: 99%